The Role of Job Satisfaction In The Effect of Quality of Work Life On Performance of Research Institution’s Employee - Nancy Yusnita; Audrey Mahrani Melati F (UNIVERSITAS PAKUAN, 2023)
This study aims to determine the This study aims to find strategies that can be implemented by management to improve employee performance of SEAMEO BIOTROP by analyze the effect of quality of work life on employee performance, the effect of job satisfaction on employee performance, the effect of quality of work life on employee job satisfaction and the effect of quality of work life on employee performance indirectly through job satisfaction. This research is a verification research. The object of this research consists of 3 (three) namely the quality of work life, job satisfaction and employee performance. The population in this study were 80 employees of the operational unit. Data collection was carried out through questionnaires and observation, the data analysis method used partial least squares (PLS) analysis. The results of the study show that the quality of work life has a direct positive effect on performance, job satisfaction has a direct positive effect on performance, then the quality of work life has a direct positive effect on job satisfaction and the quality of work life has an indirect positive effect on performance through job satisfaction. It can be concluded that the intervening variable (job satisfaction) acts as a mediator between the quality of work life and employee performance.